Methodological approach to determining the main factors for the development of creative thinking in students of creative professions - Kryshtanovych, Myroslav; Kryshtanovych, Svitlana; Stepanenko, Liudmyla; Brodiuk, Yuliіa; Fast, Alina (Creativity Studies, 2021)
The phenomenon of a person’s creative thinking, as well as the mechanisms of its development,are in the problematic field of research of numerous scientists for many centuries. The relevance of these problems was reinforced in many respects by the desire of a person to understand his capabilities, to use them in order to create a comfortable environment around him. Interest in this problem at this stage of socio-historical development has its own special features.The questions that are raised in the study are what factors have the most significant influence on the development of creative thinking in students of creative professions. The main purpose of the article is to determine and compile the key factors for the development of creative thinking in students of creative professions as the main guarantee of their success. To do this, we have applied the methodology of the graph connections between the main factors, which will allow us to form a methodological approach to the hierarchical ordering of the most important factors in the development of creative thinking in students of creative professions as the main guarantee of their success. The subject of the research is the factors of influence on the creative thinking of students of creative specialties. The results of the study led to the formation of the key factors influencing the development of creative thinking among students of creative professions through expert analysis and a survey of specialists in this field and literature. The practical value of the study is to determine the key factors of influence on the development of creative thinking in students and the possibility of using the proposed methodological approach, in particular. The study has limitations and they consist because the process of determining the key factors for the development of creative thinking in students of creative professions took place only considering the specifics of the activities of educational institutions in Ukraine.